Microbiology for the health sciences - Burton, Gwendolyn R. W.; Engelkirk, Paul G. (Philadelphia : Lippincott Williams & Wilkins, 2004)
"This premier text in basic microbiology is designed for a broad range of students including those with little or no science background. Coverage consists of the beneficial and harmful activities of microbes, and includes the core themes outlined for an introductory course by the American Society for Microbiology."--Jacket.
Sect. I Introduction to microbiology -- Ch. 1 Microbiology: the science -- Ch. 2 Microscopy -- Sect. II Introduction to microorganisms -- Ch. 3 Cell structure and taxonomy -- Ch. 4 Diversity of microorganisms: acellular and procaryotic microbes -- Ch. 5 Diversity of microorganisms: eucaryotic microbes -- Sect. III Chemical and genetic aspects of microorganisms -- Ch. 6 Biochemistry: the chemistry of life -- Microbial physiology and genetics -- Sect. IV Controlling the growth of microorganisms -- Ch. 9 Using antimicrobial agents to control microbial growth in vivo -- Sect. V Environmental microbiology -- Ch. 10 Microbial ecology -- Ch. 11 Epidemiology and public health -- Sect. IV Microbiology in healthcare facilities -- Ch. 12 Healthcare epidemiology: nosocomial infections and infection control -- Ch. 13 Diagnosing infectious diseases -- Sect. VII Pathogenicity and host defense mechanisms -- g Ch. 14 Pathogenesis of infectious diseases -- Ch. 15 Nonspecific host defense mechanisms -- Ch. 16 Specific host defense mechanisms: an introduction to immunology -- Sect. VIII Infectious diseases -- Ch. 17 Major viral, bacterial, and fungal diseases of humans -- Ch. 18 Major parasitic diseases of human: an introduction to medical parasitology -- App. A Compendium of important bacterial pathogens of humans -- App. B Useful conversions -- Index.
Includes bibliographical references and index.
Keywords: MICROBIOLOGY; MEDICAL MICROBIOLOGY; ALLIED HEALTH PERSONNEL; COMMUNICABLE DISEASES